2016
DOI: 10.7759/cureus.545
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Osteomyelitis of the Spine Following Intravesical BCG Therapy for Bladder Cancer

Abstract: Osteomyelitis is an infection of the bone that can involve the vertebral column. A rare cause of vertebral osteomyelitis is Mycobacterium bovis after intravesical Bacillus Calmette-Guerin (BCG) therapy for transitional cell carcinoma of the bladder. In this report, we describe the case of a 64-year-old male presenting with constitutional symptoms, progressive thoracic kyphosis, and intractable T11 and T12 radiculopathies over the proceeding six months. A CT scan revealed erosive, lytic changes of the T12 and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 34 publications
(67 reference statements)
0
38
0
Order By: Relevance
“…T12 to L4. Secondarily, as recently suggested [28], through the vertebral venous plexus (known as Batson's venous plexus). Once again, a venous spread of BCG does not explain thoracic osteomyelitis.…”
Section: Pathogenesis Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…T12 to L4. Secondarily, as recently suggested [28], through the vertebral venous plexus (known as Batson's venous plexus). Once again, a venous spread of BCG does not explain thoracic osteomyelitis.…”
Section: Pathogenesis Discussionmentioning
confidence: 96%
“…However, other distant infections are described in the literature, mostly vascular aneurysms in a recent literature review [43], but also disseminated infections also called BCGitis [44], small-vessel central nervous system vasculitis [45] and even nosocomial infections, including vertebral osteomyelitis [46]. Some risk factors of distant infections could be suggested: a traumatic catheterisation during instillation [5], haematuria, instillations in the few days around an urological trauma [28] (pelvic radiation, surgery, bladder resection), arterial catheterisation [13], and general immunosuppressive factor such as HIV infection.…”
Section: Pathogenesis Discussionmentioning
confidence: 99%
“…Intravesical BCG therapy for the treatment of superficial bladder cancer has a low risk of extravesical complications, which are rare (5), but adverse effects such as cystitis, a fever, hematuria, prostatitis, arthralgias, and reactive arthritis are relatively common. The first study to mention tuberculous spondylitis caused by intravesical BCG therapy was reported in 1992, but only 13 cases related to intravesical BCG therapy for bladder cancer have been reported since (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) (Table). In most cases, BCG spondylitis develops several months after intravesical BCG therapy, while some cases may develop several years later, but the cause is unknown (13).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1976, BCG has been administered intravesically to treat transitional cell carcinoma of the bladder, and has proven to be a safe and effective therapy for various carcinomas in situ [1] , [2] . It comes with potential side effects [3] , where serious reactions may occur in less than 5% of patients [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Osteitis is rare following BCG immunization, occurring in less than 37 per 100,000 cases [2] . As of 2016 there were only 16 cases of vertebral osteomyelitis secondary to intravesical BCG reported in the English literature [1] . Venous translocation via the Batson plexus or hematogenous spread are postulated mechanisms for dissemination [1] .…”
Section: Introductionmentioning
confidence: 99%